Relationship of Community traffic rights and international conventions - Đurđev, Dušanka (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
The Lisbon Treaty has established the Union as a legal personality . It opens for mixed agreements on foreign policy and community topics. In areas where the Union legislates, the EU can sign various kinds of agreements on behalf of the member states, who are consequently not allowed to negotiate international agreements on their own (autonomously) in these areas. The European Union’s accession to the Convention concerning International Carriage by Rail (COTIF) represents a historic step for the railway community. This relationship is now  clear: a disconnection clause in the accession agreement in principle allows EU law precedence for traffic internal to the EU. The relationship between EU law and COTIF law is there more about coordination than disconnection.